Clinical features of muscle cramp in 14 dogs. (28th November 2020) - Gagliardo, Teresa; Ruggeri, Roberta; Di Paola, Andrea; Baroni, Massimo; Cherubini, Giunio B.; Gallucci, Antonella; Falzone, Cristian; Trimboli, Stefania; Albul, Andrey; Gandini, Gualtiero
Abstract: Background: Muscle cramps (MCs) are prolonged, involuntary, painful muscle contractions characterized by an acute onset and short duration, caused by peripheral nerve hyperactivity. Objectives: To provide a detailed description of the clinical features and diagnostic findings in dogs affected by MCs. Animals: Fourteen dogs. Methods: Multicenter retrospective case series. Cases were recruited by a call to veterinary neurologists working in referral practices. Medical records and videotapes were searched for dogs showing MCs. The follow‐up was obtained by telephone communication with the owner and the referring veterinarian. Results: Three patterns of presentation were identified depending on the number of affected limbs and presence/absence of migration of MCs to other limbs. In 9/14 (64%) of dogs, MCs were triggered by prompting the dogs to move. 8/14 (58%) dogs were overtly painful with 6/14 (42%) showing mild discomfort. The cause of MCs was hypocalcemia in 11/14 (79%) dogs: 9 dogs were affected by primary hypoparathyrodism, 1 dog by intestinal lymphoma and 1 dog by protein losing enteropathy. In 3/14 cases (21%) the cause was not identified, and all 3 dogs were German Shepherds. Conclusions and Clinical Importance: Muscle cramps can manifest in 1 of 3 clinical patterns. Muscle cramps are elicited when dogs are encouraged to move and do not always appear as painful events, showing in some cases only discomfort. The main cause of MCs in this study was hypocalcemia consequent to primary hypoparathyroidism. In dogs having MCs of unknown etiology, idiopathic disease or paroxysmal dyskinesia could not be ruled out.